(untitled) (Global Journal of Human-Social Science, 2020)
Since Nigeria’s independence in 1960, Nigerian politics has been bedeviled by ethnic politics as a result of ethnic polarization and sentimental coloration of all national issues. This problem has been one of the major factors inhibiting national integration and national development in Nigeria. Nigerian politics is tainted with ethnic sentiments and politically induced disharmony. Ethnic politics has been one of the factors responsible for low productivity and the general poor socio -economic development in Nigeria. The major focus of this study is to examine the challenges of ethnic politics in Nigeria as it relates to national integration with a view to critically evaluating the impact. Secondary data was used to gather relevant information for this study. One finding of the study is that ethnic politics was deliberately introduced and propagated in the Nigerian political system by the British colonial government through its divisive ’divide and rule’ policy to actualize colonial and imperialist economic and political objectives. The situation has not abated in spite of several attempts to redress it through state creation and the Federal character principle.